ENDOUROLOGIC MANAGEMENT IN NEGLECTED DOUBLE J STENT AT SOETOMO HOSPITAL SURABAYA RETROSPECTIVE-DESCRIPTIVE STUDY, PERIODE 2013-2016 - Fathurrahman, Hasroni; Hakim, Lukman (Indonesian Urological Association, 2020)
Objective: The use of various combinations of endourological techniques can be an effective solution in the management of neglected DJ stent. The variety of treatments that combine the extracorporeal shock wave lithotripsy (ESWL), retrograde cortolithotripsy (CLT) ureteroscopy with intracorporeal lithotripsy, percutaneous nephrolithotomy (PCNL) and open surgery have been used for the management of encrustation stent cases in a neglected DJ stent. Material & Methods: A Retrospective descriptive study by evaluating patients that have done undergoing endourological measures in the case of Neglected DJ stents in Soetomo General Hospital from January 2013 to December 2016. Data analysis based on age, gender, location of encrustation, indication of DJ stent insertion, duration of DJ stent insertion, and type of endourologic management. Results: In this study, the data of patients undergoing endourological action in Neglected DJ stent cases were 29 patients from January 2012 to December 2016. In Neglected DJ stent patients (41.4%) 12 were encrusted and (58.6%) 17 that there is no encrustation. From 29 patients neglected DJ stent, consisting of (20.7%) 6 males and (79.3%) 23 females, with ratio male to female 1:4, the incidence of DJ stent encrustation was 12 with ratio male to female 1:1, with ages ranging from 41-64 years. The most common cause of DJ stent insertion in Neglected DJ stent patients was malignancy that cause obstructive uropathy (72.4%) 2, all of them were female patients, followed by ureteral stones (24.1%) 7, where males (13.8%) 4 and women (10.3%) 3, and UPJ stenosis where there were only (3.4%) 1 men. In the neglected dentist stent there were 62 (62%) 18 unilateral stent (males (13.8%) 4 and female (48.3%) 14 while the bilateral stent were (37.9%) 11, where male (6.9%) 2 and female (31%) 9. Duration of DJ stent use in neglected DJ stent is higher in 15 weeks (20.7%) 6, followed by 17 weeks (17.2%) 5, 14 weeks (13.8%) 4, 16 weeks, 18 weeks, 20 weeks each (10.3%) 3, 13 weeks (6.9%) 2, and last order during 19 weeks, 26 weeks, 29 weeks each (3.4%) 1. Where the largest organ there is encrustation is Ureter (24.1%) 7, followed by renal with a kidney (10.3%) 3. After which the kidneys with ureter (3.4%) 1 and buli (3.4%) 1. Management of Neglected DJ stent without encrustation performed procedure of removing DJ stent 17 (58.6%), while management of Neglected DJ stent with stent encrustation. The majority procedure was URS (13.8%) 4, followed by URS + PCNL and ESWL pre op + URS respectively (6.9%) 2, and few with ESWL preoperative procedures, CLT, CLT + PCNL, and ESWL pre operation + CLT + PCNL about (3.4%) 1. Conclusion: The neglected ratio male to female 1:4, while the incidence of DJ stent encrustation was 12 with ratio male to female 1:11. The most common cause of DJ stent insertion in Neglected Dj stent patients was malignancy that cause obstructive uropathy, followed by ureteral stones and UPJ stenosis Patients with unilateral DJ stent more than those with bilateral DJ stent. Duration of DJ stent usage in Neglected DJ stent at most for 15 weeks and last order for 19-29 weeks. In Neglected DJ patients the patient incrustation ratio and no incrustation were 2:3. Management of the Neglected DJ stent without encrustation is performed by DJ stent with cystoscopy, while the management of the Neglected DJ stent with encrustation is performed with a multimodal endourology procedure, among others: a combination of URS, PCNL, ESWL pre-op and CLT. The most commonly organ that have encrustation is the ureter, the second sequence is the bladder with the kidney, and finally the kidney with the ureter and the bladder.